Post-partum psychosis: socio-demographic and obstetric profile - Ahuja, Sunil Kumar; Mishra, Nimisha; Kumar, Pradeep (International Journal of Research in Medical Sciences, 2017)
Background: Better knowledge of socio-demographic profile and obstetric features may help in early identification and treatment of patients with post-partum psychosis. The aim of present research is to study the age, parity, socio-demographic and obstetric and menstrual profile of patients suffering from post-partum psychosis. Setting and Design: A cross-sectional study at in-patient department of psychiatry, SS Medical College and associated SGMH Rewa. Methods: The study was conducted on sixty patients of post-partum psychosis admitted in psychiatry ward. Detailed socio-demographic characteristics, obstetric and menstrual profile along with psychiatric assessment were recorded in proforma specially designed for the study. Results: Bulk of our post partum psychotic subjects (60%) were in the age range of 18-25 years with 83.33% of women were residing at rural areas. Most of subjects (76.67%) of post partum psychosis were illiterate. 73.33% patient were belonging to low socio-economic status and remaining to middle and high socioeconomic status. Majority of subjects (13.33%) were house wife (86.67%) followed by laborer class. Family jointness reveal 80% and 20% of subjects trailed from joint and nuclear family respectively. the maximum number of subjects (60%) were primipara with only 13.33% of subjects had history of obstetric complication in form of prolonged labour and post-partum heamorrhage. 25% subjects had cesarean delivery. 40% patients of puerperal psychosis were having menstrual irregularity and 60% had regular menstruation. Conclusions: Screening of vulnerable groups i.e. younger age, primipara, history of irregular menstruation in post partum period for psychiatric sign and symptoms is requisite for early diagnosis and prompt and adequate management. As most of the patients were from rural areas it is necessary to establish psychiatric services in rural areas as well so that this group of population can be provided holistic care along with already existing medical services.